Factors affecting access to early postnatal care service among women of urban slum in Bangladesh - Hasan, Mohammad A.; Mujahid, M. Arif A. (International Journal Of Community Medicine And Public Health, 2023)
Background: Postnatal care (PNC) refers to care and attention to the general mental and physical health of the mother and infant during the period beginning after the delivery of the placenta up to the next six weeks. The postnatal period, the hours and days after birth is critical to the health for survival and is the most vulnerable time for a mother and newborn. Majority of maternal death occur after delivery but the postnatal period is the most ignored time for the establishment of quality services yet now in Bangladesh. The aim of the study was to assess the factors affecting access to early postnatal care service among women of urban slum in Bangladesh. Methods: This was a community based cross sectional descriptive quantitative study conducted among the women of reproductive age who gave birth in the last one year prior to the study period in different slums of Dhaka South City Corporation, Dhaka, Bangladesh during the period from September to October 2016. A stratified sampling method was employed to select the total of 382 study participants for this study. Data were collected by means of a pretested structured interviewer administered questionnaire. Chi square and binary logistic regression analysis was carried out by using statistical package for the social sciences (SPSS) version 21.0. Results: In this study, it was found that, 29.1% women and 29.8% of their baby received postnatal care service (PNC) visit after last delivery. The factors that significantly affected the access to postnatal care service utilization in this study were women’s education, household income, residence, husband’s education and occupation, physical violence against women, place of delivery, ANC visit, PNC checkup for baby, postnatal complications, importance of PNC checkup, knowledge in PNC service, perception of postnatal danger sign, sources of information, transport use, and health insurance. In assessing all those factors, the p values were found as <0.001. Conclusions: Among the common factors affecting access to early postnatal care service among women of urban slum, domestic physical violence against women and health insurance emerged as strong predictors. In Bangladesh there is a crucial need for public health interventions to increase the access rate to early postnatal care service that should target women who need this service at the appropriate time.